Implementasi Kebiasaan Shalat Dhuhur dan Dhuha Berjamaah dalam Meningkatkan Kedisiplinan dan Kebiasaan Siswa di SDN Sumbersari 2 Malang - Wahyudi Widodo (ARZUSIN, 2026)
Although the habituation of religious activities has the potential to develop students’ discipline and positive habits, studies on its implementation within elementary school culture remain limited. This study aimed to describe the implementation of the habituation of congregational Dhuhr and Duha prayers in improving students’ discipline and positive habits at SDN Sumbersari 2 Malang. This study employed a qualitative approach with a descriptive design. The research informants consisted of the principal, Islamic Religious Education teachers, classroom teachers, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing. The findings showed that the habituation of congregational Dhuhr prayer for students in Grades III–VI was conducted every day except Friday, whereas practical instruction in the Duha prayer was implemented in Islamic Religious Education classes and reinforced through monthly congregational Duha prayers accompanied by the recitation of shalawat and istighasah. The consistent implementation of the program established a religious school culture and improved students’ discipline, as reflected in punctuality, compliance with school regulations, and responsibility in performing religious practices. The program also developed positive habits, including maintaining cleanliness, observing proper order during ablution, respecting peers, and cooperating throughout the activities. The successful implementation of the program was supported by teachers’ exemplary conduct, the principal’s commitment, the involvement of all school community members, and continuously implemented habituation. These findings affirm that the habituation of congregational prayer can serve as a strategy for strengthening character education by developing discipline and positive habits among elementary school students. Keywords: Student Discipline; Character Education; Religious Habituation; Congregational Prayer; Elementary School